COGNITIVE BEHAVIORAL THERAPY PRACTICES FOR CRIMINALS - MANMOHAN KUMAR (International Journal of Multidisciplinary Research and Studies, 2021)
Cognitive Behavioral Therapy is not a single method of psychotherapy; rather, CBT is an umbrella term for therapies with many similarities. CBT is a marriage of sorts between social learning theory, cognitive therapy, and behavioral therapy, all of which initially grew from experimental psychology. From the cognitive therapist’s perspective, an individual’s personality is formed by central values that have developed early in life as a result of factors in the individual’s environment. These factors serve as the basis for the way the individual codes, categorizes, and evaluates their experiences and the stimuli they encounter. Cognitive therapists believe that psychological problems stem from faulty learning, making incorrect assumptions as the result of inadequate or incorrect information, and not being able to adequately distinguish between imagination and reality.